The Role of Interoceptive Attention and Appraisal in Interoceptive Regulation - Joshi, Vrutti; Graziani, Pierluigi; Del-Monte, Jonathan (Frontiers in Psychology, 2021)
Interoception, i.e. the processing and integration of sensory information has gained research interest due to its relevance in the psychopathological context. In the present review, we focus upon interoceptive regulation or one’s capacity to match bodily signals to his/her desired state by altering the signal or the desired state. More specifically, we discuss attention towards and appraisal of interoceptive stimuli as regulatory mechanisms of interoception. We review findings in the emerging research area of interoceptive attention. Studies suggest that the quality of attention and the nature of appraisal regarding interoceptive information influence interoceptive regulation and subsequent adaptive or maladaptive behavioural strategies among healthy controls as well as clinical populations. We discuss the clinical implications and the need to promote further research as well as to target interoceptive attention and appraisal mechanisms in psychotherapy.